Systematic Approach to Modernization of the Russian Federal Spatial Development - A. I. Tatarkin (Образование и наука)
The paper estimates the regional and municipal opportunities of spa- tial development modernization in the Russian Federation. In the post-crisis period, it is necessary to facilitate the innovative processes and society oriented state develop- ment to give way to the steady transition from the regional policy to the federal state structure, which requires scientifically based decision making in all the directions of social development. The author considers the ideology of such transition and recom- mends using the systematic approach to choosing priorities and development institu- tions. Several perspective factors such as education and science are analyzed in the context of systematic regional and territorial development along with the necessity for program-project modernization of the federal state structure. The following new insti- tutions for regional development are proposed: regional and municipal self-deve- lopment, business territories, program-project planning of spatial development.